Shelf life Enhancement of Hardhead Catfish (Aris felis) Patties Making Use of Acetic Acid Induced Gelation of the Fish Proteins - S.B., Warrier; G.K., Smruti; V, Yardi; S.V., Sherekar; V., Venugopal (Fishery Technology, 2025)
Hardhead catfish (Aris felis) meat was collected by mechanical deboning. A portion of the meat mince was converted into a gel by repeated washing in cold water followed by lowering its pH to 3.5 using acetic acid. The gel was also diluted in water to give a dispersion having a viscosity of 0.60 Pa.s. Patties from the catfish mince were prepared using a standard recipe. In some of the patties, the fish mince was replaced with the meat gel at a concentration of 10% (w/w). A few of the gel-incorporated patties were also given a coating with the gel dispersion. The patties containing the gel, coated with the dispersion or both were stored at 1-30C At periodic intervals, samples were analyzed for microbial and sensory quality. Sensory evaluation of the patties was conducted after shallow frying the product in refined vegetable oil. Incorporation of gel together with dispersion coating suppressed microbial growth in the product during storage. The product had a refrigerated shelf life of 3 weeks in comparison with a 2 week shelf life for the untreated patties, patties containing the gel, or those coated with the dispersion alone. The process of gel incorporation and dispersion coating offered a method for extended storage and distribution of catfish patties under chilled conditions.